2002
DOI: 10.1136/bjo.86.4.373
|View full text |Cite
|
Sign up to set email alerts
|

Moderate visual impairment in India: the Andhra Pradesh Eye Disease Study

Abstract: Aim: To assess the prevalence and demographic associations of moderate visual impairment in the population of the southern Indian state of Andhra Pradesh. Methods: From 94 clusters in one urban and three rural areas of Andhra Pradesh, 11 786 people of all ages were sampled using a stratified, random, cluster, systematic sampling strategy. The eligible people were invited for interview and detailed dilated eye examination by trained professionals. Moderate visual impairment was defined as presenting distance vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
181
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(192 citation statements)
references
References 8 publications
7
181
4
Order By: Relevance
“…In men, visual impairment did not have a significant relationship with age. Blindness and visual impairment has been reported to be higher in women in studies conducted in India, 16 Rotterdam, 6 Melbourne, 17 Oman, 18 and Meiktila. 19 On the other hand, some studies have reported blindness and visual impairment to be higher in men.…”
Section: Discussionmentioning
confidence: 99%
“…In men, visual impairment did not have a significant relationship with age. Blindness and visual impairment has been reported to be higher in women in studies conducted in India, 16 Rotterdam, 6 Melbourne, 17 Oman, 18 and Meiktila. 19 On the other hand, some studies have reported blindness and visual impairment to be higher in men.…”
Section: Discussionmentioning
confidence: 99%
“…3 Wearing spectacles is not only a social stigma but also has tremendous impact on the psychological development of a child. 4,5 Now, it is worth a thought why don't children like spectacles. This study was conducted to understand the common perceptions in children about the use of spectacles as well as refractive errors and problems faced by these children while using spectacles.…”
Section: Introductionmentioning
confidence: 99%
“…Similar observations were made by Patil B et al from their study done in Karnataka. [7] Patients above the age of 65 years were significantly less in number. This finding was comparable to study findings made by .…”
Section: Discussionmentioning
confidence: 99%
“…There have been many surveys done abroad [3][4] and inside India [5][6][7][8][9][10] Section: Ophthalmology of blindness. The current study finding of more males having a visual disability than the females was found to be similar to the findings made by other study groups.…”
Section: Discussionmentioning
confidence: 99%